Key factors determining the development of SARS-CoV-2 testing strategies in EU countries: a mixed-methods study - M C de Vries; A Timen; L S Kengne Kamga; A C G Voordouw; M P G Koopmans (BMJ Public Health)
Background The WHO and the European Center for Disease Prevention and Control (ECDC) advocated for extensive testing as a crucial pillar in managing the COVID-19 pandemic. Yet, public health emergency responses varied across European countries. In particular, there were differences in the national laboratory capacities and diagnostic testing strategies. This study was conducted during the pandemic to identify the key factors in developing national, SARS-CoV-2 testing strategies across a selection of European countries.Methods A mixed-methods study, comprising an interview phase and a survey phase, was performed. First, laboratory, policy-making and/or public health experts from different European countries were interviewed between 8 January 2021 and 19 March 2021, to review the development and implementation of national testing strategies.Second, a cross-sectional survey was conducted among ECDC National Focal Points (NFP) for Preparedness and Response and/or Microbiology between July and October 2022 to validate the interview findings.Results 12 European experts were interviewed and identified the following key factors determining the development of the national SARS-COV-2 testing strategies in their countries: (1) changing testing goals over time, (2) the prevailing epidemiological situation, (3) testing capacities, (4) availability of reference laboratories, (5) supply and stockpiling of testing material, (6) availability of human resources and (7) quality management standards across laboratories. The experts interviewed stressed the important role of stockpile management, the existence of expert networks, as well as the centralisation of decision-making. Lastly, determining the actors responsible for the testing strategy and putting in place ‘coordination, accountability and governance’ proved to be pivotal.The survey outcome with 15 European NFPs demonstrated that the testing strategies generally changed over time to include a broader group of individuals. Furthermore, the actors ‘Ministry of Health’, ‘Public health officials’, ‘National public health institutes’ and ‘National Expert and/or advisory groups’ were selected as key players by survey respondents.Conclusions In general, the scope of the testing strategy in European countries included in this study expanded as the pandemic progressed. This study identified key factors discussed by European experts interviewed that contributed to the development of SARS-CoV-2 testing strategies across European countries.